Enhancing Student Understanding of Newton's Laws Through the PODEW Analogy-Based Strategy in High School Physics - Hidayat, Taufik; Wasis, W; Suprapto, Nadi; Diantoro, Markus; H, Supriyono Koes; Hidaayatullaah, Hasan Nuurul; Mapandi, Rohanie D (Indonesia Approach Education, 2024)
Students frequently encounter alternative conceptions regarding physics, both before and after studying physics concepts. This study aims to examine the effectiveness of the PODEW (Predict, Observe, Discuss, Explain, Write) strategy integrated with analogy-based learning in addressing these misconceptions. A mixed-method explanatory model was employed, involving both quantitative and qualitative approaches. Quantitative data were collected through pretests and posttests and analyzed using ANCOVA, N-Gain calculations, and effect size measurements. Qualitative data were obtained via interviews with selected students to provide further insights into the findings. The study involved 60 high school students from State Senior High School of Pandewu 1, with Grade 10 Science-1 (experimental group) utilizing the PODEW strategy with analogy and Grade 10 Science-2 (control group) employing the PODEW strategy without analogy. Results indicated a significant difference between the two groups, with the experimental group achieving an N-Gain score of 0.64 compared to 0.48 in the control group, indicating greater improvement in addressing alternative conceptions. Despite these improvements, some students in the experimental group shifted from scientific understanding to alternative conceptions, suggesting the need for further refinement of the strategy. Overall, the findings highlight the potential of the PODEW strategy with analogy in reducing misconceptions and improving students' conceptual understanding of Newton's Laws.